How to test the effect of aspirin and clopidogrel in patients on dual antiplatelet therapy?. (2nd January 2016) - Bagoly, Zsuzsa; Homoródi, Nóra; Kovács, Emese Gyöngyvér; Sarkady, Ferenc; Csiba, László; Édes, István; Muszbek, László
Abstract: Dual antiplatelet therapy with clopidogrel and aspirin is frequently used for the prevention of recurrent ischemic events. Various laboratory methods are used to detect the effect of these drugs administered in monotherapy, however their value in dual therapy has not been explored. Here, we determined which methods used for testing the effect of clopidogrel or aspirin are influenced by the other antiplatelet agent. One arm of the study included 53 ischemic stroke patients being on clopidogrel monotherapy showing effective inhibition of the P2Y12 ADP receptor. Laboratory tests routinely used for the detection of aspirin resistance (arachidonic acid (AA)-induced platelet aggregation/secretion, AA-induced thromboxane B2 (TXB2 ) production in platelet-rich plasma and VerifyNow Aspirin assay) were carried out on samples obtained from these patients. The other arm of the study involved 52 patients with coronary artery disease being on aspirin monotherapy. Methods used for testing the effect of clopidogrel (ADP-induced platelet aggregation and secretion, flow cytometric analysis of vasodilator-stimulated phosphoprotein (VASP) phosphorylation and a newly developed P2Y12 -specific platelet aggregation (ADP[PGE1 ] test)) were performed on samples obtained from these patients. Clopidogrel monotherapy significantly inhibited AA-induced platelet aggregation and secretion, moreover, AA-induced TXB2 production was also significantly decreased. VASP phosphorylation and AA-induced platelet aggregation showed fair correlation in patients taking clopidogrel only. Clopidogrel did not inhibit the VerifyNow Aspirin test significantly. Aspirin monotherapy influenced ADP-induced platelet aggregation and secretion, but did not have an effect on VASP phosphorylation and on the ADP[PGE1 ] platelet aggregation test.